First-principles study of binary FCC Fe-Mn compositions - Phasha Maje; Mampuru Lebedike; Mkhonto Donald; Moema Joseph (MATEC Web of Conferences)
In a build-up to design and development of light-weight austenitic Fe-Mn alloys for storage and transportation of liquefied natural gas (LNG), present study employed computational materials modelling technique to identify compositions that yield high toughness at cryogenic temperatures. This study revealed that the addition of manganese (Mn) resulted in an increase in lattice constant and convex-shaped heats of formation trend with minimum at 22 atomic percent (at.%) Mn alloy composition. In addition, increase in Mn composition yielded a significant decrease in tetragonal shear modulus (C′) and Young’s modulus (E), while the decrease in bulk modulus (B) is small. Ductility increased with increase in Mn composition as shown by B/G and Poisson’s ratio (v) values that are much higher than ductility threshold of 1.75 and 0.26, respectively, signalling high toughness.